Evolution of the real area of contact during laboratory earthquakes - Baoning Wu; Sylvain Barbot (Proceedings of the National Academy of Sciences, 2025)
Empirical slip-rate- and state-dependent friction laws and linear fracture mechanics constitute popular approaches to explaining earthquakes. However, the physics underlying friction laws remain elusive and fracture mechanics does not specify fault strength at the various conditions relevant to crustal faulting. Here, we introduce a physical constitutive framework that augments the traditional approaches by incorporating the real area of contact as the state variable. The physical model explains the dynamics of slow and fast ruptures on transparent materials, as well as the amount of light transmitted across the interface during laboratory ruptures. The constitutive framework elucidates the origin of empirical friction laws, and the simulated ruptures can be described by linear elastic fracture mechanics. Continuous measurements of the physical state variable or its proxies during seismic cycles emerge as a novel tool for probing natural faults and advancing our understanding of the earthquake phenomenon.